Electronic design of portable ECT for crude palm oil quality monitoring system - Mohamad, Elmy Johana; Abdul Rahim, Ruzairi; Rahiman, Mohd Hafiz Fazalul; Mohd Muji, Siti Zarina (ICIC International, 2012)
This paper presents the process of visualizing the composition of a crude palm oil (CPO) during separator process which collects the recovered crude palm oil from the liquid waste before separation process, in order to monitor the percentage· of load waste p1·esent using a tomographic technique by Portable. Electrical Capacitance Tomography (ECT) so that the process separation {separate oil and water/sludge) becomes much easier and the quality of crude palm oil can be reliably monitored. Palm oils industry is one of the largest production, producer and exporter of palm oil and palm oil products countries in the world. Oil Palm was first introduced to Malaysia in year 1875 as an ornamental plant. .Malaysia has the mast ideal climate conditions for growing oil palm. The growth of the palm oil industry in Malaysia has been phenomenal over the last 4 decades. Nevertheless, palm oil industry is one of the most pollution generating agro industries in Malaysia. One of the major problems arises from the oil palm fruit processing is the large amount of wastes generated during the processes. There are two main wastes resulted from operation of a Palm Oil Mill, namely solid waste and liquid waste. The solid waste may consist of palm Kernel shells, mesocary fibers and empty fruit bunches. The liquid waste generated from extraction of palm oil of a wet process comes mainly from oil room after separator or decanter. There is no monitoring system that is currently available in our local palm oil mill to visualize the percentage of load waste present inside the vessel. Therefore, the system is aimed to become an instrument to support the local and foreign palm oil mills to efficiently control in monitoring the quality of crude palm oil flow in the conveying pipeline during extraction of palm oil mill process. The monitoring system is able to visualize the percentage of load waste present inside the vessel so that the data can be used to design better process equipment in mill process or to control certain processes in order to maximize the quality of crude palm oil and the POME treatment process can be improved.